Praktek Islam di Era Media Global: Konvergensi Media Sosial sebagai Sumber Ilmu Pengetahuan Agama Islam - Prastyo, Tri Budi; Fat Hanna, Risda Alfi; Yusufa, Uun; Fikra, Hidayatul (Jurnal Riset Agama, 2021)
Social media in this digital era has become a source of concentration in information. Not a few uses of social media as a source of knowledge in religious values (Islam). This study aims to discuss the practice of Islam in the global media era of social media convergence as a source of Islamic religious knowledge. The research uses a qualitative approach through descriptive-analytical methods. The results and discussion of this study indicate that the facts that we can see today, there are a lot of misleading, gossiping and immoral actions that originate from various content available on social media, of course, it becomes homework for all, especially parents, teachers and preachers so that they can help. educate the younger generation so that they become wiser and smarter in using social media. This study concludes that in a religious context, the convergence of social media as a source of knowledge has both positive and negative impacts. This study recommends all social media users to continue to adopt sciences whose sources of references and learning narrations are clear, especially on religious issues (Islam).